Architectural solutions of testing network for mobile operators - Kashtanov, I. V.; Arhelyuk, O. D. (Видавництво Національного університету "Львівська політехніка", 2009)
The present paper aims at revealing of the main elements of the GSM network, the relationship between the subsystems of Telco-part and integrated IP-functional, such as billing-platform and additional services. The model of integration of VPN-functional in the operator testing network is proposed and the scheme of the signal exchange for incoming and outgoing calls involving VPN-platform is represented. Research is conducted on the basis of a real GSM-system. As practice shows, the test fragments in the network are an integral part of the functional network. Due to the test fragments it is possible completely to eliminate the risk factors in the integration of any equipment or functionality to the network operator, to reduce financial losses in migratory operations. With a help of the test network it became possible to provide «painless» to the core network training and professional development of specialists, who in future will operate the equipment, which is also one of the main expenditure items of telecommunication operator.
Keywords: MS; BSS; NSS; interface; SS7